1998
DOI: 10.1097/00005373-199810000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Systemic Fat Embolization after Medullary Canal Pressurization

Abstract: This study is the first to show that intravascular fat persists in the lungs, kidneys, and brain for 72 hours after canal pressurization and, by itself, does not cause pathologic evidence of acute inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…It has been suggested that the monomer causes systemic vasodilatation (Peebles et al 1972, Berman et al 1974, Samii et al 1980. However, the currently accepted mechanism is the microembolisation of the arterioles and capillaries in the lungs due to the extravasation of bone marrow particles, leading to cardiovascular deterioration (Breed 1974, Orsini et al 1987, Wheelwright et al 1993, Schemitsch et al 1998, Aebli et al 2002. Other explanations have included a nerve reflex triggered by the increase in pressure within the bone marrow cavity during manipulations (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the monomer causes systemic vasodilatation (Peebles et al 1972, Berman et al 1974, Samii et al 1980. However, the currently accepted mechanism is the microembolisation of the arterioles and capillaries in the lungs due to the extravasation of bone marrow particles, leading to cardiovascular deterioration (Breed 1974, Orsini et al 1987, Wheelwright et al 1993, Schemitsch et al 1998, Aebli et al 2002. Other explanations have included a nerve reflex triggered by the increase in pressure within the bone marrow cavity during manipulations (i.e.…”
mentioning
confidence: 99%
“…In the past, different animal models have been used to investigate FE (Breed 1974, Rudigier and Ritter 1983, Orsini et al 1987, Wheelwright et al 1993, Schemitsch et al 1998. Recently, an animal model of vertebroplasty has been developed to investigate FE (Aebli et al 2002).…”
mentioning
confidence: 99%
“…This may be a result of the vulnerability of the lung tissue due to high blood circulation and accumulation of systemically released inflammatory mediators and immune cells. Furthermore, Schemitsch et al [31] reported lung injury without associated systemic inflammation might be related to the liberation of fat content after long-bone fractures. OPN, a component of extracellular bone matrix, is a protein with diverse functions in the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…21 Further studies in animal models have shown that intravascular fat appears to produce a negligible inflammatory response. 27,31,32 The importance of fat as a cause of ARDS in the multiply-injured patient therefore remains in doubt. 33 There is often ample evidence of other secondary triggers for ARDS after injury, 34,35 and the role of FE is difficult to define.…”
Section: Fat Embolisation After Fracture: Is It Important?mentioning
confidence: 99%